Digital and Competing Information Sources: Impact on Environmental Concern and Prospects for Cooperation - Vladimir Udalov; Paul J. J. Welfens (Institute of Labor Economics (IZA), 2017)
The environmental concern of people in industrialized and developing countries is analysed. Using the 2010-2014 wave of the World Value Survey (WVS), the main purpose of our analysis is to investigate the effect of different information sources on the affective, conative and behavioural components of the environmental concern of people in the developed and developing countries. As independent variables we use a set of economic data as well as information-related variables, including the internet, mobile phones, TV, radio and newspapers. The digital variables of the internet and mobile phones turn out to have a highly significant impact on environmental concern so that digital modernization of countries should have pro-environmental impacts as a side-effect of internet and mobile phone services expansion. With the developing countries catching-up vis-à-vis the OECD countries in the field of mobile phone density and internet density, respectively, one may expect better prospects for cooperation between developed and developing countries since attitudes/the environmental concern of people in developed and developing countries will become more similar an effect that is reinforced through the income variable.
Keywords: Q50; D10; C83; D80; 330; environmental concern; World Value Survey; mass media; information technologies; international economics